Abnormal behavior detection of human by video surveillance system - Amin, Anisul; Anzum, Mohammad Farhan; Mondol, Mark Himel (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.